2018
DOI: 10.5944/openpraxis.10.4.917
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in Access to, and the Use and Sharing of (Open) Educational Resources among Students and Lecturers at Technical and Comprehensive Ghanaian Universities

Abstract: This paper is the second in a series of three with a common goal to present a fair OER picture for Sub-Saharan Africa, represented by large-scale studies in three countries: Kenya, Ghana, and South Africa. This paper examines a deliberate selection of four Ghanaian universities with randomly sampled students and lecturers. Distinct questionnaires for students and the lecturers have been used, which generated a response from in total 818 students and 38 lecturers. The major outcomes based on the empirical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…In particular, schools tend to establish their own resource management platform, which greatly increases the cost of repeated development, resulting in a huge waste of resources. erefore, realizing effective sharing of educational resources without infringing intellectual property rights has become an important challenge and urgent problem to be solved for educational informatization [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, schools tend to establish their own resource management platform, which greatly increases the cost of repeated development, resulting in a huge waste of resources. erefore, realizing effective sharing of educational resources without infringing intellectual property rights has become an important challenge and urgent problem to be solved for educational informatization [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, the findings indicated that whether and how OER adoption takes place at an institution are shaped by a layered sequence of factors such as infrastructural access, legal permission, conceptual awareness, technical capacity, material availability, and individual or institutional volition that are further influenced by prevailing cultural and social variables [ 55 ]. One study of [ 63 ] provided insights on the awareness and appreciation of the OER concept, and open licensing is low, but there is a ready step for openness in the future.…”
Section: Resultsmentioning
confidence: 99%
“…[ 67 ] further pointed out that to facilitate OER adoption in Africa, more focus should be put on in-service OER training and teacher professional development. [ 63 ] underlined that lack of common understanding of OER as well as the needed competence and experience limit OER adoption. [ 51 ] emphasized that there are barriers to the operationalization of OER, and research participants have knowledge and understanding of OER but this has not been translated into active participation.…”
Section: Resultsmentioning
confidence: 99%
“…Hylén ( 2020)'e göre AEK, toplumlar tarafından istişare içerisinde ve ticari amaç gütmeden hazırlanan tüm kaynakları ifade etmektedir. Bu açıklamalar üzerinden değerlendirildiğinde, AEK'lerin sürekli devam eden bir gelişme sürecinde olduğu ve her geçen gün popülerlik kazandığı yorumu yapılabilir (Black, 2023;Feder, 2023;Pete, Mulder, Neto ve Omollo, 2018).…”
Section: Açık Eğitim Kaynaklarıunclassified